2020
DOI: 10.1007/s00531-020-01848-2
|View full text |Cite
|
Sign up to set email alerts
|

Variscan eclogites from the Argentera–Mercantour Massif (External Crystalline Massifs, SW Alps): a dismembered cryptic suture zone

Abstract: We document structural, geochemical, petrological and 40 Ar/ 39 Ar geochronological data performed on Variscan eclogites from the Argentera-Mercantour Massif, southwestern Alps. Based on the high-resolution field mapping, we present new eclogite occurrences and discuss the relationships between eclogites and surrounding migmatites. We recognized for the first time preserved eclogite facies assemblages. Trace elements and REE patterns establish that eclogites protoliths are MORBs contaminated by continental cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 151 publications
3
28
0
Order By: Relevance
“…For highest convergence velocities, metamorphic imprints characterized by low P/T ratios can diffusely coexist with metamorphic imprints distinguished by high P/T ratios and lying along gradients traditionally associated to cold and warm subduction complexes, as described by Cloos (1993) (see dashed‐dotted and continuous arrows in Figure 13). Such observation well fits, for example, with the occurrence in the Variscan subduction complex of blueschist‐ to granulite‐facies conditions (e.g., Ballèvre et al., 2009; Faure et al., 2005; Jouffray et al., 2020; Lardeaux, 2014b), in accordance with higher velocities generally proposed for the Variscan convergence (Regorda et al., 2020, and refs. therein).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For highest convergence velocities, metamorphic imprints characterized by low P/T ratios can diffusely coexist with metamorphic imprints distinguished by high P/T ratios and lying along gradients traditionally associated to cold and warm subduction complexes, as described by Cloos (1993) (see dashed‐dotted and continuous arrows in Figure 13). Such observation well fits, for example, with the occurrence in the Variscan subduction complex of blueschist‐ to granulite‐facies conditions (e.g., Ballèvre et al., 2009; Faure et al., 2005; Jouffray et al., 2020; Lardeaux, 2014b), in accordance with higher velocities generally proposed for the Variscan convergence (Regorda et al., 2020, and refs. therein).…”
Section: Discussionsupporting
confidence: 88%
“…P-T conditions predicted by the models are also consistent with the contrasted P-T metamorphic conditions and gradients that have been described in the internal zones of some collisional belts. Significantly contrasted P-T metamorphic conditions have been recorded during the Variscan subduction, from blueschist, to eclogite and HP-granulite facies (e.g., Ballèvre et al, 2009;Faure et al, 2005;Jouffray et al, 2020;Lardeaux, 2014b;Regorda et al, 2020), as observed in all models (Figure 5).…”
Section: Discussionmentioning
confidence: 72%
“…They all derive from normal to enriched MORB‐type tholeiites emplaced during the Ordovician between ca. 480 and 450 Ma (Jouffray et al., 2020; J. L. Paquette et al., 1989; Rubatto et al., 2010; Von Raumer & Bussy, 2004), presumably in a thinned continental crust during the opening of the Rheic and Saxo‐Thuringian oceans. Peak pressure is constrained between 1.3–1.8 GPa and 650–750°C (Ferrando et al., 2008; Liégeois & Duchesne, 1981; Vanardois et al., 2020; this work), and is followed by near‐isothermal decompression to ca.…”
Section: Discussionmentioning
confidence: 99%
“…They all derive from normal to enriched MORB-type tholeiites emplaced during the Ordovician between ca. 480 and 450 Ma (Jouffray et al, 2020;J. L. Paquette et al, 1989;Rubatto et al, 2010;Von Raumer & Bussy, 2004), presumably in a thinned continental crust during the opening of the Rheic and Saxo-Thuringian oceans.…”
Section: Carboniferous Hp Metamorphism In the Ecmmentioning
confidence: 99%
“…In the Helvetic zone, the Variscan basement is exposed in the External Crystalline massifs of Argentera, Pelvoux, Grandes Rousses, Belledonne, M t -Blanc, Aiguilles Rouges, and Aar-Gothard (Figures 5 and 6). Due to the weakness of the Alpine overprint, the pre-Permian geology of the External Crystalline massifs has been investigated since a long time (e.g., [4,9,13,36,38,[53][54][55][56][57][58][59]). However, the widespread crustal melting erased the early structures.…”
Section: The Variscan Belt In the West Alpine Helvetic Basementmentioning
confidence: 99%